Labeling Live Cells by Copper-Catalyzed Alkyne-Azide Click Chemistry - Hong, Vu (2010)
The copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction, optimized for biological molecules in aqueous buffers, has been shown to rapidly label mammalian cells in culture with no loss in cell viability. Metabolic uptake and display of the azide derivative of N-acetylmannosamine developed by Bertozzi, followed by CuAAC ligation using sodium ascorbate and the ligand tris(hydroxypropyltriazolyl)methylamine (THPTA), gave rise to abundant covalent attachment of dye-alkyne reactants. THPTA serves both to accelerate the CuAAC reaction and to protect the cells from damage by oxidative agents produced by the Cu-catalyzed reduction of oxygen by ascorbate, which is required to maintain the metal in the active +1 oxidation state. This procedure extends the application of this fastest of azide-based bioorthogonal reactions to the exterior of living cells.